Hydrochemical characteristic and karst development in typical karst spring area, Northern China - Xiaojuan, Qiao; Baoling, Li; Kai, Liu; Xinyu, Chai; Wenjin, Yu (Frontiers in Environmental Science, 2025)
Karst aquifer is controlled by complex tectonics. While the tectonic effects and its relationship with chemical evolution in large-scale karst areas are always be neglected. This study focuses on the relationship and systematically analyzed structure control on hydrochemical indicators for karst development in Fangshan, Beijing, North China. The results show that the hydrochemical type changes from mainly HCO3-Ca·Mg, HCO3-SO42--Ca·Mg, to HCO3-Mg·Ca along with the flow. The ions relationship, Gibs and SI analysis show the process is mainly rock weathering. From recharge to the discharge area, the increases of Mg2+ mainly due to dedolomitization process and the desulfation results in sulfate reduction. Total dissolved solid (TDS) increases from 261 to 630 mg/L along the flow. While, its core around the fracture-intensive zone is low (less than 247 mg/L). And higher Sr concentration neighboring lamprophyre (χ) and magmatic rock (γ). It proved that the overprint of two-episodic tectonism processes caused a series of NE-NW fold-back thrust nappe structures and a number of faults intersection areas, effects hydrochemical characteristic. The direction of a series of karst caves is consistent with the direction of the Xiayunling fold-back thrust nappe structure indicates that multi-stage tectonic activity creates runoff channels and WRI space and impact cave distribution. Our work is benefit to understanding the role of fractures on karst development from the perspective of hydrochemical view in the groundwater flow, which can provide a basis for further formulating the planning of karst water exploitation.